Le e-learning à l’ère de la covid 19 à l’université algérienne : état des lieux, défis et perspectives - Djamaleddine Nouredine (Multilinguales)
Our contribution is part of the presentation of a vision of a new teaching-learning mode that is currently being experimented with at Algerian universities, namely E-learning. This is a simplified presentation of the nature of E-learning, in order to define all the sectors and spheres linked to this new teaching approach, and to determine the properties and transformations brought about by this tool in the Algerian higher education process. Secondly, we carried out an online questionnaire survey of a group of 3rd-year students in the Applied Sciences Department at Ibn-Khaldoun University in TIARET, during the covid-19 pandemic, to assess the effectiveness of the tool and, at the end, propose resolutions that would contribute to its improvement, which obviously requires answers to two major questions : What challenges do universities face in involving teachers and students in the online teaching process ? What are the appropriate means for successful online teaching during the covid-19 health crisis ?